The Impact of Dynamic Capabilities on Innovation and Performance of Culinary Creative Enterprises - Hatidja; Bahtiar; Jamaluddin; Asriani (PT. Anagata Sembagi Education, 2026)
The culinary creative industry is one of the most dynamic and competitive subsectors of the creative economy, particularly in developing economies such as Indonesia. This study examines the impact of dynamic capabilities on innovation and business performance among culinary creative enterprises. Using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 203 owners and managers of culinary micro, small, and medium enterprises (MSMEs) in Central Java through purposive sampling. Dynamic capabilities were operationalized through three dimensions: sensing, seizing, and reconfiguring. The findings reveal that dynamic capabilities positively and significantly influence innovation (path coefficient = 0.487, p < 0.001) and business performance (path coefficient = 0.312, p < 0.001). Innovation also significantly mediates the relationship between dynamic capabilities and business performance (path coefficient = 0.206, p < 0.001), confirming a partial mediation effect. These results underscore the critical role of cultivating adaptive organizational capabilities as a competitive lever in volatile markets. The study contributes novel empirical evidence from the culinary creative economy context, bridging gaps between dynamic capability theory and creative industry performance in an emerging market setting.